Phenotypic variability in a large Czech family with a dynamin 2-associated Charcot-Marie-Tooth neuropathy - Haberlová, J; Mazanec, R; Ridzoň, P; Baránková, L; Nürnberg, G; Nürnberg, P; Sticht, H; Huehne, K; Seeman, P; Rautenstrauss, B (Journal of neurogenetics, 2011)
Mutations in the Dynamin 2 gene (DNM2) cause autosomal dominant centronuclear myopathy or autosomal dominant (AD) Charcot-Marie-Tooth (CMT) disease. Here the authors report one large Czech family with 15 members affected with an AD CMT phenotype of extraordinary variability. Genetic linkage analysis using SNP arrays revealed a locus of about 9.6 Mb on chromosome 19p13.1-13.2. In this critical interval, 373 genes were located. The only gene herein known to be associated with an intermediate type of CMT was Dynamin 2 (DNM2). Subsequent sequence analysis of the DNM2 gene in the index patient revealed a novel missense mutation p.Met580Thr. This missense mutation segregated with the neuropathy, indicating the causal character of this mutation. The phenotype of CMT in this family shows mild to moderate impairment with relatively preserved upper limbs and a very broad range of the onset of clinical symptoms from an early onset around the age of 12 to the late onset during the fifth decade. Electrophysiology showed an intermediate type of peripheral neuropathy. The motor median nerve conduction velocity varied from 36 m/s to normal values with signs of asymmetrical affection of peripheral nerves. No additional symptoms such as cranial nerve involvement, cataract, and signs of neutropenia or myopathy syndrome were observed in any member of the family yet. The progression was slow with no loss of ambulation. The authors suggest that the characterization of clinical variability in a single family may help to direct the genetic analysis directly to the rarely observed DNM2 mutations.
Keywords: Young Adult; Charcotova-Marieova-Toothova nemoc; Mutation, Missense; Czechoslovakia; fenotyp; Male; Pedigree; Phenotype; Child, Preschool; Dynamin II; missense mutace; rodokmen; Genetic Predisposition to Disease; Charcot-Marie-Tooth Disease; mladý dospělý; Adolescent; Infant; Child; dítě; Adult; dospělí; mužské pohlaví; mladiství; novorozenec; předškolní dítě; lidé; ženské pohlaví; Humans; Československo; Infant, Newborn; kojenec; Female; lidé středního věku; dynamin II; genetická predispozice k nemoci; Middle Aged